(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
In this paper a fault tree technique is used as a system safety analysis, it is a top-down deductive analysis structured in terms of events rather than components. For analysis system safety gates and rules of Boolean algebra are applied to determining cut sets which represents quantitative and qualitative analysis with illustrative examples. Conclusion: 1.The use of FT technique determines the minimal cut sets of systems which in term is very useful in lowering the maintenance cost for the aim of the safety to make empty from hazards. We can find the reliability of any system and identify the risk areas for that system and through them we can determine the integrity of the system. The most important and commonly used tools of evaluating system reliability is the fault tree method, which can be used to find and analyze the integrity of the system as it gives more accurate and reliable results.